Holographic mode field generation for a multimode fiber channel - Amphawan, Angela; O'Brien, Dominic (2010)
For a conventional launch into an MMF, a large number of modes are excited, entailing significant modal dispersion and limiting the bandwidth of the MMF link. To mitigate modal dispersion in MMF, a new single mode field generation technique using a transmissive spatial light modulator and a set of lenses is proposed and demonstrated experimentally. The rapid reconfiguration speed of the SLM surmounts the mode switching limitations of previous single mode field generation techniques while allowing for adaptive updating of the incident field on the MMF. For modes up to azimuthal and radial mode numbers of 4, the generated modal electric fields achieved high power coupling efficiencies, in the range of 90.15% to 95.79%.